Addressing an urgent global public health need: Strategies to recover routine vaccination during the COVID-19 pandemic. Issue 1 (31st January 2022) - Larson, Anna; Skolnik, Ava; Bhatti, Alexandra; Mitrovich, Rachel
ABSTRACT: Routine vaccination has been severely impacted by the COVID-19 pandemic, with 37% of countries reporting continuing disruptions to vaccination services into 2021. These programs have been faced with the challenges of achieving high vaccination coverage rates (VCRs), as well as identifying and vaccinating those who missed recommended doses since the pandemic began. Declines in VCRs, even for short periods, can lead to an increase in disease outbreaks, place additional pressure on health systems, and leave communities across the world at risk of death and disease from vaccine-preventable diseases. In the face of these disruptions, select governments are implementing promising approaches to address low VCRs, some of which represent innovative solutions to advance short-term, as well as longer-term program improvement. However, expanded action is urgently required to fully recover vaccination programs and strengthen vaccine system infrastructure. The COVID-19 pandemic provides a unique opportunity to modernize routine programs and corresponding infrastructure to meet today's and tomorrow's health challenges more effectively and efficiently. This can be achieved by prioritizing routine vaccination as an essential health service, improving access to vaccination across the life-course, strengthening data systems, ensuring sustainable immunization financing, and building confidence in vaccination.